Answer:
h(x) = 2^(x) - 1.
Step-by-step explanation:
Let's look at each equation:
f(x) = -3x +7, Well as x increases, since it's multiplication, there are "going to be more" -3's, so it's going to be decreasing.
g(x) = -4(2^x). While 2^x is increasing, because "there are going to be more 2's multiplied by each other" as x increases, it's being multiplied by a negative number, so it's actually going to be decrasing
h(x) = 2^(x) - 1. Here's it's going to be increases as x goes towards infinity because "there are going to be more 2's multiplied by each other", and there isn't any negative sign, while there is a negative 1, it's constant, so the overall value will be increasing
Answer:
T.A = 54 + 9/2 √3
Step-by-step explanation:
∵ The figure is triangular prism
∴ T.A = perimeter of the base × height + 2 × area of the base
∵ The base is an equilateral Δ with side length 3"
∴ The perimeter of the base = 3 × 3 = 9 inches
∴ The area of the base = 1/4 S² √3 = 1/4 (3)²√3 = 9/4 √3 inches²
∵ The length of the height of the prism = 6"
∴ T.A = 9 × 6 + 2 × 9/4 √3 = 54 + 9/2 √3
∴ T.A = 54 + 9/2 √3 inches²
Answer:
6.6
Step-by-step explanation:
Answer: 7
Step-by-step explanation: